Psychometric properties of the Multidimensional Health Locus of Control Scale: Ukrainian sample - Danyliuk, Ivan; Kurapov, Anton; Malysheva, Karine; Yahiiaiev, Illia; Loshenko, Oleksandra; Lytvyn, Serhiy (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2023)
B a c k g r o u n d . Health control and management are important processes, the relevance of which has increased after the COVID-19 pandemic. Health control is equally important for the population of Ukraine today. Various assessment methodologies are used to measure health control, and the MHLC is one of the most commonly used, and also showed high reliability in several countries worldwide. Considering the importance of the issue and constant threat to the health of population, the necessity of having this scale available in Ukrainian is clear.Correspondingly, the present study aimed to adapt the MHLC (Multidimensional Health Locus of Control) scale to the Ukrainian context and to test the psychometric properties of the scale for its suitability for use among the Ukrainian-speaking population.M e t h o d s . The properties of the MHLC scale were evaluated on a sample of 392 respondents from Ukraine. The psychometric properties were assessed using the following statistical tests: reliability and internal consistency (Cronbach's alpha), factor analysis (exploratory and confirmatory), and correlation analysis.R e s u l t s . Cronbach's alpha for the MHLC scale was 0,72. EFA analysis revealed the presence of a three-factor model structure. The model's goodness-of-fit indicators are as follows: χ2 = 389, p < 0,001; CFI = 0,86; TLI = 0,84), SRMR = 0,06, AIC = 22982, BIC = 23209. The main factors of the model are: influential others, internal, and randomness. The correlation analysis revealed a strong relationship between the MHLC scale items and the 5C scale items, which confirms convergent and discriminant validity.C o n c l u s i o n s . The Ukrainian version of the MHLC scale has positive psychometric characteristics and can be used in studies focused on the Ukrainian-speaking context and sample. Validation procedure showed the ability of Ukrainian scale to match the initial five factors suggested by the authors of the scale.
Keywords: multidimensional health locus of control; MHLC; psychometric characteristics; adaptation; validation